Effects of Biochar on Soil Quality in a Maize Soybean Rotation on Mollisols - Likun Hou; Yuchao Wang; Zhipeng Wang; Ruichun Gao; Xin Zhou; Siyu Yang; Xu Luo; Zhenfeng Jiang; Zhihua Liu (Agronomy)
Rotation and organic material addition (e.g., biochar) are major measures to improve soil quality, but the improvement effects and mechanisms of their combination on soil quality remain unclear; the relationship between the physical, chemical, and biological parameters was has not been adequately detected in terms of the change in quality after biochar addition. This study selected corn straw biochar as the material and established two biochar application methods: biochar mixed in 0–20 cm soil depth (B1) and biochar mixed in 0–40 cm soil depth (B2). After 3 years of maize–bean rotation, soil samples from 0–20 cm and 20–40 cm were collected to determine the soil’s physical, chemical, and biological properties, as well as crop yields. Principal component analysis was used to establish a minimum data set for the systematic analysis of soil quality and its factors. The results showed that compared with the control (CK), biochar reduced soil bulk density by 3.1% and electrical conductivity by 19.5–28.25% while increasing soil organic matter content by 7.2%, ammonium nitrogen content by 6.7–12.0%, available nitrogen content by 6.7–18.5%, available phosphorus content by 15.6–23.8%, available potassium content by 11.6–17.3%, soil urease activity by 12.25–21.6%, soil sucrase activity by 6.8–30.8%, soil neutral phosphatase activity by 5.6–9.7%, and soil catalase activity by 13.6%. Four indicators, namely bulk density, water content, pH, and nitrate nitrogen, were selected from 16 soil-quality-related indicators to form the minimum data set (MDS), and the soil quality index was calculated. Biochar application significantly increased the soil quality index (SQI) of rotation soil by 14.6–63.3% and crop yields by 5.6–7.2%. A random forest analysis of soil indicators and crop yields, combined with partial least squares structural equation modeling, revealed that biological indicators—particularly catalase activity—showed significant positive correlations with crop yields. Based on these multi-dimensional analyses, the interaction between rotation systems and biochar application improves the quality of mollisol soil plow layers by reducing bulk density and increasing catalase activity.